Effectiveness and safety of PD-1/PD-L1 or CTLA4 inhibitors combined with chemotherapy as a first-line treatment for lung cancer: A meta-analysis - Shen, Kaikai; Cui, Jinggang; Wei, Yuqing; Chen, Xiaojun; Liu, Guohua; Gao, Xiaolai; Li, Wei; Lu, Huiling; Zhan, Ping; Lv, Tangfeng; Lin, Dang (Journal of Thoracic Disease, 2018)
Background: Immune checkpoint inhibitors (ICIs) combined with chemotherapy have been applied as a first-line treatment for lung cancer, but consistent beneficial results have not been documented. Therefore, our meta-analysis aimed to evaluate the effectiveness and safety of combination therapy to promote its application. Methods: We searched electronic databases for studies that estimated the safety and efficacy of combined therapy. The objective response rate (ORR) and disease control response (DCR) parameters were evaluated with odds ratio (OR) values of the combination arm over the non-combination arm. Hazard ratios (HR) and its 95% confidence intervals (95% CI) were used to calculate progression-free survival (PFS) and overall survival (OS) in the combination and non-combination arms. All treatment-related adverse events (TRAEs) and 3 to 5 TRAEs were expressed as relative risk (RR) values of the combination arm over the non-combination arm. Results: Ten eligible studies involving 4,887 patients were identified. The pooled ORs for ORR and DCR were 1.85 (95% CI: 1.30–2.63, P